MENINGKATKAN HASIL BELAJAR MELALUI PENDEKATAN PEMBELAJARAN SAINTIFIK MATA PELAJARAN PAI KELAS VIII B DI SMP MUHAMMADIYAH 08 CAKRU - Nur Raissatur Rohmah (PGMI Department of Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia, 2023)
The scientific learning approach is learning that focuses on students being more active in the classroom. This learning model has good steps including observing, collecting data, reasoning and communicating. This learning model provides students with the opportunity to think critically in learning activities. The aim of this research is to improve student learning outcomes through a scientific learning approach in class VIII b PAI subjects at SMP Muhammadiyah 08 Cakru. This type of research is classroom action research with the number of samples in this research being 21 students in class VIII B at SMP Muhammadiyah 08 Cakru. The data collection technique is by conducting observations and writing tests. Meanwhile, when observations were made, the results obtained were 3 students (14%) with an average score of 70-80 who achieved completeness and students (86%) with an average score of 40-70 who still had not achieved completeness. After the first cycle of action was carried out, the increase was 14 students (67%) who completed it with an average score of 70-90 and 7 students (33%) who had not achieved completeness with an average score of 40-60. Then the second cycle of action was carried out which then it increased again, namely 17 students (81%) completed with an average score of 70-90 and 4 students (19%) had not yet achieved a completion score with an average score of 40-60. Based on research results, it shows that student learning outcomes increase by using a scientific learning approach model for class VIII b students in PAI subjects at SMP Muhammadiyah 08 Cakru.